Framework for developing extensible and reusable parallel and distributed applications - Ribeiro Justo, G.R.; Freire Cunha, P.R. (Proceedings of 1996 IEEE Second International Conference on Algorithms & Architectures for Parallel Processing, ICA³PP '96 : June 11-13, 1996, Singapore, 1996)
The number of parallel and distributed programming languages available is enormous. This means that the user faces a difficult task in selecting the language which suits his/her application. Most of the facilities supported by new languages could be, however, introduced as simple extensions of existing languages. In object oriented languages where the concepts of reusability and extensibility are natural parts of the language, extensions can easily take place by creating frameworks which provide the abstraction level required by the user. We present a framework that supports the dynamic reconfiguration of processes. C++CL is a framework developed in C++ and layered above PVM. This means that dynamic reconfigurable systems are easily built in a C++ fashion following the CL approach. At the same time, by using PVM, we improve the portability of the framework over heterogeneous networks and can also use all tools available for tracing and debugging PVM parallel processes. The paper then shows how the framework can be extended to provide special classes of programs.